Pengaruh Crowes Fraud Pentagon dalam Mendeteksi Kecurangan Pelaporan Keuangan - Shella Gilby Sapulette; Kathleen Asyera Risakotta (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2020)
This study aims to obtain empirical evidence and to examine the elements of fraud in fraud pentagon theory against indications of fraudulent financial reporting on 42 leasing companies listed in the Indonesia stock exchange (BEI) period 2016-2018. Independent variables in this research were financial target, external pressure, ineffective monitoring, change in auditor, change of director, and frequent number of CEO’s picture, while the dependent variable was fraudulent financial reporting which measured using earnings management (DACC). This research use multiple linear regression method with 21 SPSS software. The results of this research shows that financial target, ineffective monitoring, and frequent number of CEO’s picture are significant in detecting fraudulent financial reporting. These variables represents three elements in fraud pentagon, namely pressure, opportunity and arrogance.